Avianue an urban avian sanctuary as an avenue for birdlife conservation, education, and rehabilitation - Lee, Camille Justine C. (College of Architecture, University of the Philippines Diliman, 2025)
Birdlife is often a neglected and overlooked part in our environment because they seemingly occupy a miniscule portion, when in fact, they are an essential part of it. Birds contribute to the overall health of the ecosystem and indicate the level of biodiversity within an area. Despite this, there is a widespread lack of public awareness on the significance of birdlife in the Philippines. The country is one of the most bird species-diverse in the world, however, birdlife faces challenges of survival within the urban landscape such as habitat loss, wildlife exploitation, public ignorance, and unsympathetic architecture in cities. There is also a lack of facilities for birdlife conservation, education, and rehabilitation, and the wildlife rescue centers that are existing are insufficient and not up to proper standard. The built environment has a crucial role in the safety and health of birdlife. Urban birds especially are more susceptible to bird glass collisions, artificial light hazards, and anthropogenic noise. The goal of the study was to propose an urban avian sanctuary that provides a safe haven for birds in the city and promotes public awareness and engagement in Philippine birdlife conservation, education, and rehabilitation. The research design strategies involved gathering secondary resources, conducting interviews, and visiting sites in Metro Manila similar to the typology of the project. The design methods used were experiential design, biophilic design, and bird-friendly design. City environments have the potential to diversify the bird ecosystem because urban green spaces have shown to serve as a habitat for them. There is also an emerging design movement called bird-friendly design which aims to make the built environment more inviting and safe for birds. Interventions such as bird deterrent glass styles, reduced artificial light, rustic and vernacular elements, walls as nesting spaces, and considerate landscaping were integrated into the design of the project. Considering the wetland and grassland site of the project, the main design approach was to minimize construction time and impact to the environment as much as possible. Straightforward, simple, and modular were used in the design and the entire structure is raised on stilts. Moreover, the built structure is limited to the edges of the site closest to the roads and perimeter trees as to not impede on the open central wetland and grassland, which is a habitat for birds. Overall, the project aims to create an urban avian sanctuary conscious of birdlife challenges and needs through architecture and planning.